1991
DOI: 10.1161/01.atv.11.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Passage state affects arachidonic acid content and eicosanoid release in porcine aortic endothelial cells.

Abstract: Porcine aortic endothelial cells were cultured through four passages from primary cultures. The arachidonic acid content of individual phospholipid classes and the release of 6-keto-prostaglandin F la and 15-hydroxyeicosatetraenoic acid in response to 1 /tM ionophore A23187 were assayed at each passage. The content of arachidonic acid in phosphatidylinositol and diacyl phosphatidylethanolamine remained constant at passage 1 but declined at passage 2 by approximately 29% and at passage 4 by approximately 59%. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In cultured endothelial cells it has been demonstrated that arachidonic acid content can decrease as much as 66% over the first four passages, and this can markedly decrease eicosanoid production. 24 This factor alone could explain the difference found in our cells, which were grown for only two passages. Also, tissues from diabetics and cells grown for several passages with serum, unlike our cells, which underwent a brief exposure to elevated glucose in PSS, are exposed to insulin, which can itself influence eicosanoid release.…”
Section: Effect Of Elevated Glucose On Eicosanoid Productionmentioning
confidence: 83%
“…In cultured endothelial cells it has been demonstrated that arachidonic acid content can decrease as much as 66% over the first four passages, and this can markedly decrease eicosanoid production. 24 This factor alone could explain the difference found in our cells, which were grown for only two passages. Also, tissues from diabetics and cells grown for several passages with serum, unlike our cells, which underwent a brief exposure to elevated glucose in PSS, are exposed to insulin, which can itself influence eicosanoid release.…”
Section: Effect Of Elevated Glucose On Eicosanoid Productionmentioning
confidence: 83%
“…The low level of prostaglandin release most likely relates to the fact that these cells were used at passage 8 as others have shown a steady loss of cyclooxygenase products in passaged EC. 24 In the cytoplasm most of the oxidized product within the cells was 12-HETE with lower levels of 11,12-EET. It should be noted that although the product identified as 11,12-EET migrates with authentic 11,12-EET in our HPLC system, it has not been chemically identified as 11,12-EET.…”
Section: Discussionmentioning
confidence: 95%
“…For example, reduced proliferative capacity, increased oxidative stress, activation of the NFj-B and p53 signaling pathways (Lee et al 2010), reduced nitric oxide production and surfactant protein D (SP-D) expression (Lee et al 2009) were detected in porcine coronary arterial endothelial cells after multiple passaging in vitro. Enhanced apoptosis of porcine pulmonary artery endothelial cells (Zhang et al 2002) and declined arachidonic acid content and eicosanoid release in porcine aortic endothelial cells in response to agonist stimulation (Brown and Deykin 1991) were determined as well. The effects of cell passaging on endothelin-1 and prostaglandin F2a production of bovine luteal endothelial cells (Acosta et al 2007) and on the responsiveness of bovine aortic endothelial cells to orbital shear stress (Kudo et al 2005) were also evaluated.…”
Section: Introductionmentioning
confidence: 99%